Diagnostic and therapeutic medical devices for safer blood management in cardiac surgery; systematic reviews, observational studies and randomised controlled trials - Murphy, G; Mumford, A; Ca, R; Wordsworth, S; Stokes, E; V., V; Kumar, T; Harris, J; Clayton, G; Ellis, L; Plummer, Z; Dott, W; et al. (National Institute for Health Research, 2017)
Background Anaemia, coagulopathic bleeding, and transfusion, are strongly associated with organ failure, sepsis and death following cardiac surgery. Aims Anaemia, coagulopathic bleeding, and transfusion, are strongly associated with organ failure, sepsis and death following cardiac surgery. Methods and Results Work Stream 1: In the COPTIC study (ISRCTN20778544) we demonstrated that risk assessment using baseline clinical factors predicted bleeding with a high degree of accuracy. The results from Point-of-Care (POC) platelet aggregometry or viscoelastometry tests or an expanded range of reference laboratory tests for coagulopathy did not improve predictive accuracy beyond that achieved with the clinical risk score alone. The routine use of POC tests was not cost-effective. A systematic review (PROSPERO CRD42016033831) concluded that POC based algorithms are not clinically effective. We developed two new clinical risk prediction scores for transfusion and bleeding that are available as e-calculators. Work Stream 2: In the PASPORT Trial (ISRCTN 23557269), and a systematic review (PROSPERO CRD4201502769) we demonstrated that personalised Near Infra-red Spectroscopy based algorithms for the optimisation of tissue oxygenation, or as indicators for red cell transfusion, were neither clinically nor cost effective. Work Stream 3: In the REDWASH trial (SRCTN 27076315) we failed to demonstrate a reduction in inflammation or organ injury in recipients of mechanically washed versus standard (unwashed) red cells. Limitations Existing studies evaluating the predictive accuracy or effectiveness of POC tests of coagulopathy, or Near Infra-Red spectroscopy were at high risk of bias. Interventions that alter red cell transfusion exposure, a common surrogate outcome in most trials, were not found to be clinically effective. Conclusions A systematic assessment of devices in clinical use as blood management adjuncts in cardiac surgery did not demonstrate clinical or cost effectiveness. Further Research The contribution of anaemia and coagulopathy to adverse clinical outcomes following cardiac surgery remains poorly understood. Further research to define the pathogenesis of these conditions may to lead to more accurate diagnosis, more effective treatments, and potentially improved clinical outcomes.